2017
DOI: 10.1016/j.cellimm.2017.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Didox (3,4-dihydroxybenzohydroxamic acid) suppresses IL-33-induced cytokine production in primary mouse mast cells

Abstract: While IgE is considered the primary mediator of mast cell activation, IL-33 contributes substantially in asthma, allergic rhinitis, and atopic dermatitis. To develop effective treatments for allergic disease, it is important to understand the role of therapeutic agents on IL-33 activation. We examined the effect of Didox (3,4-dihydroxybenzohydroxamic acid), an antioxidant and ribonucleotide reductase (RNR) inhibitor, on IL-33-mediated mast cell activation. Didox suppressed IL-6, IL-13, TNF, and MIP-1α (CCL3) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…These results corroborate previous research, where Didox treatment antagonized pro-inflammatory responses of anti-CD3-activated T cells and LPS-stimulated macrophages in allotransplant and macrophage inflammatory disease models, respectfully [17,18]. Additionally, these data agree with Didox effects on IL-33-mediated mast cell activation [19]. Collectively, these results indicate Didox may have broad anti-inflammatory effects.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These results corroborate previous research, where Didox treatment antagonized pro-inflammatory responses of anti-CD3-activated T cells and LPS-stimulated macrophages in allotransplant and macrophage inflammatory disease models, respectfully [17,18]. Additionally, these data agree with Didox effects on IL-33-mediated mast cell activation [19]. Collectively, these results indicate Didox may have broad anti-inflammatory effects.…”
Section: Discussionsupporting
confidence: 91%
“…In addition to antiproliferative effects, Didox possesses antioxidant and anti-inflammatory activity with significant therapeutic potential to treat diseases associated with oxidative stress and inflammation [17,18,38]. We have recently published Didox suppression of IL-33 mediated mast cell activation [19], however IgE-mediated mast cell function has not been studied. Here we investigated Didox effects in vitro and in vivo and the implications they may have for treating allergic inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, a number of studies have identified compounds that inhibit IL-33 mediated activation of MCs. Amongst those are natural compounds from plants like berberine ( 111 ), methoxyluteolin ( 112 ), and resveratrol ( 113 ) or ES-62 produced from parasitic worms ( 114 ) as well as various other drug classes including didox (synthetic ribonucleotide reductase inhibitor) ( 115 ), chondroitin sulfate (glycosaminoglycan) ( 116 ), triochastatin A (histone deacetylase inhibitor) ( 117 ) and the growth factor TGFb1 ( 118 ). However, in all these studies, drug effects were investigated exclusively in vitro .…”
Section: Therapeutic Targeting Of the Il33-mc Axismentioning
confidence: 99%